PSEUDOACROMEGALY: A CASE OF SEVERE INSULIN RESISTANCE WITH ACROMEGALIC FEATURES AND LOW IGF-1 - Jordan Hoo, Ching Bing; Sim, Sing Yee; Florence Tan, Hui Sieng (2025)
INTRODUCTION/BACKGROUND Severe insulin resistance (SIR) is typically associated with well-established metabolic conditions such as central obesity, glucose intolerance, hypertension, dyslipidaemia, and metabolic dysfunction-associated fatty liver disease (MAFLD). We present a case of SIR with prominent dermatologic and acral manifestations mimicking acromegaly, highlighting the importance of recognizing skin and soft tissue changes as possible indicators of underlying insulin resistance.